The Neurobiology of Decision-Making and Responsibility: Reconciling Mechanism and Mindedness - Shadlen, Michael N.; Roskies, Adina L. (Frontiers in Neuroscience, 2012)
This essay reviews recent developments in neurobiology which are beginning to expose the mechanisms that underlie some elements of decision-making that bear on attributions of responsibility. These “elements” have been mainly studied in simple perceptual decision tasks, which are performed similarly by humans and non-human primates. Here we consider the role of neural noise, and suggest that thinking about the role of noise can shift the focus of discussions of randomness in decision-making away from its role in enabling alternate possibilities and toward a potential grounding role for responsibility.